PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) UNTUK MENINGKATKAN KEMAMPUAN APRESIASI SENI TARI DAERAH SISWA KELAS V SDN 164 PEKANBARU - Wardani, Dwikha Putri; Antosa, Zariul; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This reseacrh aimed to improve the ability of appreciation of regional dance by using VCT learning model. This research is Classroom Action Research (PTK) with 2 cycles in 1 cycle consist of 2 meetings. The location of this research in SDN 164 Pekanbaru with the research subjectsm is students of class V SDN 164 Pekanbaru, consist of 38 students, 21 male and 17 female students. Research Instruments are observation sheets of teacher activity, observation sheest of student activity, test sheets of appreciation ability. Data analysis technique was descriptive quantitative. The results showed that application of VCT learning model can improve the student appreciation ability regional dance. The results showed that VCT learning model can improve the appreciation ability of regional dance. Students’ ability appreciation average in base grade was 51.84 in the less favorable category. In the first cycle of first meeting, the average of students' appreciation ability was 61,97 in good enough category. Furthermore, at the second meeting increased to 66.84 in the category quite well. In the first cycle of the second meeting, the average ability of students' appreciation was 74.07 in good enough category. Furthermore, at the second meeting it becomes 81.71 in either category.Key Word :Value Clarification Technique, Ability of Appreciation